2018
DOI: 10.1002/prca.201800086
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of Uterosacral Ligament Connective Tissue from Women with and without Pelvic Organ Prolapse

Abstract: Purpose: Damage to the uterosacral ligaments is an important contributor to uterine and vaginal prolapse. The aim of this study is to identify differentially expressed proteins (DEPs) in the uterosacral ligaments of women with and without pelvic organ prolapse (POP) and analyze their relationships to cellular mechanisms involved in the pathogenesis of POP. Experimental design: Uterosacral ligament connective tissue from four patients with POP and four control women undergo iTRAQ analysis followed by ingenuity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…After that, the PD software was used to perform a quantitative analysis based on the search results and selected mass spectra. In the proteomic analysis, a fold change >1.2 was regarded to indicate a DEP between two groups according to previous studies ( 18 20 ). According to the outcome of the quantitative analysis, all identified DEPs were subjected to functional annotation using the GO ( ) and KEGG databases ( ).…”
Section: Methodsmentioning
confidence: 99%
“…After that, the PD software was used to perform a quantitative analysis based on the search results and selected mass spectra. In the proteomic analysis, a fold change >1.2 was regarded to indicate a DEP between two groups according to previous studies ( 18 20 ). According to the outcome of the quantitative analysis, all identified DEPs were subjected to functional annotation using the GO ( ) and KEGG databases ( ).…”
Section: Methodsmentioning
confidence: 99%
“…These proteins may be involved in the pathophysiology of POP. Further proteomic analysis of the etiology and pathogenesis of POP using HPLC-MS/MS, iTRAQ, and ingenuity pathway analysis (IPA) techniques described by Li et al ( 98 ), revealed five differentially expressed proteins (fibromodulin, collagen alpha-1 [XIV] chain, calponin-1, tenascin, and galectin-1) that appear to be involved in Metabolic mechanisms of the pelvic floor connective tissue. Wang et al ( 99 ).…”
Section: Other Potential Biomarkersmentioning
confidence: 99%